2021
DOI: 10.2478/prilozi-2021-0030
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Proteomics in Kidney Transplantation

Abstract: Although kidney transplantation is the best treatment option for end stage kidney disease, it is still associated with long-term graft failure. One of the greater challenges for transplant professionals is the ability to identify grafts with a high risk of failure before initial decline of eGFR with irreversible graft changes. Transplantation medicine is facing an emerging need for novel disease end point-specific biomarkers, with practical application in preventive screening, early diagnostic, and improved pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Prior observations suggested that a single biomarker is not likely to reflect the complex pathophysiological process in solid organ transplantation. 31,159 This notion, combined with the advent of a plethora of computational methods, has justified the preference toward the development of proteomic classifiers or protein panels. Additionally, integration of proteomics data with those from other techniques, such as genomics, transcriptomics, and metabolomics, is expected to provide more comprehensive snapshots and a deeper understanding of the mechanisms involved in the pathophysiology after solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior observations suggested that a single biomarker is not likely to reflect the complex pathophysiological process in solid organ transplantation. 31,159 This notion, combined with the advent of a plethora of computational methods, has justified the preference toward the development of proteomic classifiers or protein panels. Additionally, integration of proteomics data with those from other techniques, such as genomics, transcriptomics, and metabolomics, is expected to provide more comprehensive snapshots and a deeper understanding of the mechanisms involved in the pathophysiology after solid organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological specimens have been harnessed for the discovery of proteomic biomarkers, including, but not limited to, tissue samples, whole-blood, serum, plasma, urine, bronchoalveolar lavage (BAL). 28,29 Because of the minimally invasive procedure through which blood 30 and urine 31 are collected, these 2 biofluids have been preferred over biopsies in studies aiming to identify markers for clinical applications.…”
Section: Technical Considerations and Biological Samplesmentioning
confidence: 99%